MULTICULTURAL VALUES IN INDONESIAN NOVELS OF THE 2000s - Suminto A Sayuti; wiyatmi Wiyatmi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study was aimed at describing multicultural values, ways of expressing multicultural values, and the dynamics of multicultural values in Indonesian novels ofthe 2000s. The study purposively selected a sample of six novels that intensely carried thetheme of multiculturalism. These were Laskar Pelangi, Larung, Jendela-jendela, Ayat-ayat Cinta,Jepun Negerinya Hiroko, and Partikel. The study used the descriptive qualitative method.The study obtained the following findings. First, there were four main multiculturalvalues: (a) apreciasion of cultural pluralism, (b) valuing of the principles of humanismand fundamental human rights (FHR), (c) responsibility of the international society, (d)responsibility of the planet earth. Second, multicultural values are expressed throughnarrative elements and become an integral part of the entire story. Third, multicultural values move in the dynamics of locality to nationality and nationality to globality. Indonesian novels of the 2000s express Indonesian people in the contexts of world nationand citizens who are multicultural, having appreciative minds towards cultural pluralism,upholding humanism and FHR, taking responsibilities of sustaining the entirety of theworld and planet earth. Keywords: multicultural, Indonesian novel, nasionality, globality, plurality